The San Francisco Estuary, USA as a reference section for the Anthropocene series. (April 2023) - Himson, Stephen; Williams, Mark; Zalasiewicz, Jan; Waters, Colin N; McGann, Mary; England, Richard; Jaffe, Bruce E; Boom, Arnoud; Holmes, Rachael; Sampson, Sue; Pye, Cerin; Berrio, Juan Carlos; et al.
A San Francisco Estuary core was analysed at high resolution to assess its component stratigraphic signatures of the Anthropocene in the form of non-native species, Hg, spheroidal carbonaceous particles, δ 13 Corg, δ 15 N, radiogenic materials, and heavy metals. Time series analysis of the core using Ti data provides a chronology to depth 167 cm into the 1960s. Below this, to depth 230 cm, the lowermost part of the core may extend to the 1950s or potentially a little earlier. The earliest anthropogenic marker recorded in the core is the excursion in Hg (beginning at 190 cm) which may denote the early 1960s and is the closest stratigraphic marker in the core to the proposed mid-20th century timing for the onset of the Anthropocene. Biostratigraphical signatures of non-native species arriving in the 1970s–1980s are widespread key markers and are significant tools for the correlation of Anthropocene deposits across the estuary. The absence of signals that indicate pre-1950s deposits precludes the use of the core to mark the Holocene–Anthropocene boundary. However, the core provides an important reference section to demonstrate the palaeontological distinctiveness of Anthropocene series deposits.